(untitled) (The International Journal for Scientific Research, 2026)
Study Objectives: The study aims to identify the extent to which mindfulness and cognitive flexibility contribute to vocational interests among academically gifted high school students in schools in the Bethlehem Governorate, and to propose a counseling program. Methodology: The study adopts the descriptive correlational approach and applied scales of mindfulness, cognitive flexibility, and vocational interests to collect data. The study sample consists of 293 academically gifted high school students from schools in the Bethlehem Governorate, selected through convenient sampling. Results: The results of the study show that the overall level of mindfulness among academically gifted high school students in the Bethlehem Governorate was high, with a mean score of 4.03. The results also show statistically significant differences in the means of mindfulness according to the gender variable in favor of females in the dimensions of (observation, non-judgment, and non-reactivity), and according to the economic level variable in the description dimension favoring the high level, and in the acting with awareness dimension, favoring both medium and high levels. The results also indicates statistically significant differences in the means of cognitive flexibility according to the gender variable in favor of females. The results further show statistically significant differences in the means of vocational interests according to the gender variable in the realistic pattern, favoring males, and in the social pattern, favoring females, and according to the place of residence variable in the intellectual pattern, favoring village residents. The results also reveals a statistically significant predictive ability at the significance level α ≤ .05 for both mindfulness and cognitive flexibility in predicting vocational interests among these students. Recommendations: The study recommends implementing counseling programs to improve mindfulness among male students, focusing on the areas where females outperformed (such as describing and non-reactivity), through activities that align with their interests.